MANAJEMEN PERKOTAAN (STUDI KASUS PENATAAN DRAINASE DI KOTA PEKANBARU) - Ahmad Fawahid; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The system to distribute rain called drainage. This system plays an important function to createa healthy environment and reduces the overbalance of water. The capacity of drainage is smaller than seedlings flood and it makes confusion of water from the canal because the drainage was stepped up and unequal structuring construction of drainage. Based on Ministry of Public Works of Indonesian Republic No.12/2014 about the implementation of drainage of urban system. The purpose of this study is to identify the drainage structuring management in Pekanbaru, Riau. The writer uses the theory from Prajudi Atmosudirdjo on M. Manulang which explains about drainage structuring management, it is includes planning, organizing, directing and controlling. This study used descriptive qualitative method. In collecting the data, the writer was used interview, observation, and documentation. The finding of this study shows that the urban management of drainage arrangement in Pekanbaru city has gone well, it can be seen from the planning, directing, and controlling system. Due to some factors which influence sustainability of governments’’ work in handling the drainage problem, it makes the result of the governments’effort was not going well and still going flood when it rain.Keyword : Urban Management, StructuringDrainage, in the public works department of housing, settlements and copyrights of pekanbaru city.